86.5k views
5 votes
Evaluate the limit using Squeeze/Sandwich Theorem:


\displaystyle \large{ \lim_(n \to \infty) (1)/(n) \cos (n \pi)/(3) }
Please show your work too — thanks!​

User Jiby Jose
by
5.0k points

2 Answers

1 vote

cos(x) is bounded between -1 and 1. So,


-1 \le \cos\left(\frac{n\pi}3\right) \le 1 \implies -\frac1n \le \frac1n\cos\left(\frac{n\pi}3\right) \le \frac1n

As n goes to infinity, both -1/n and 1/n converge to 0, so


\displaystyle\lim_(n\to\infty)\frac1n\cos\left(\frac{n\pi}3\right) = \boxed{0}

as well.

User Ashton Honnecke
by
5.3k points
3 votes

Answer:


\displaystyle \lim_(n\rightarrow \infty)\left[(1)/(n)\cos\left((n\pi)/(3)\right)\right]=0

Explanation:

The squeeze theorem states that if
g(x)\leq f(x)\leq h(x) for all
x\\eq c in some interval around
c and
\displaystyle \lim_(x\rightarrow c)g(x)=L and
\displaystyle \lim_(x\rightarrow c)h(x)=L, then it follows that
\displaystyle \lim_(x\rightarrow c)f(x)=L.

Essentially what this is saying is that if a function
g is always smaller than or equal to function
f in some interval and a function
h is always greater than or equal to
f in the same interval, if
g and
h approach the same value at some point,
f must also approach that point, since it is being "squeezed", hence the name squeeze theorem.

Recall that the maximum output of cosine is 1 and the minimum output of cosine is -1. A quick check on the unit circle will confirm this.

Therefore, the function
\displaystyle (1)/(n)(1) will always be greater than or equal to
\displaystyle (1)/(n)\cos\left( (n\pi)/(3)\right) and the function
\displaystyle (1)/(n)(-1) will always be less than or equal to
\displaystyle (1)/(n)\cos \left((n\pi)/(3)\right).

Hence,
\displaystyle -(1)/(n)\leq (1)/(n)\cos\left( (n\pi)/(3)\right)\leq (1)/(n)\text{ for all } x\in \mathbb{R}.

We can easily compute
\displaystyle \lim_(n\rightarrow \infty)\left[- (1)/(n)\right] and
\displaystyle \lim_(n\rightarrow \infty)\left[(1)/(n)\right] with direct substitution.

Therefore, we have:


\displaystyle \lim_(n\rightarrow \infty)\left[- (1)/(n)\right]=-(1)/(\infty)=0\\\\\displaystyle \lim_(n\rightarrow \infty)\left[ (1)/(n)\right]=(1)/(\infty)=0

Since
\displaystyle \lim_(n\rightarrow \infty)\left[- (1)/(n)\right]=\displaystyle \lim_(n\rightarrow \infty)\left[ (1)/(n)\right]=0 and
\displaystyle -(1)/(n)\leq (1)/(n)\cos\left( (n\pi)/(3)\right)\leq (1)/(n), then from the squeeze theorem,
\displaystyle \lim_(n\rightarrow \infty)\left[(1)/(n)\cos\left((n\pi)/(3)\right)\right]= \lim_(n\rightarrow \infty)\left[- (1)/(n)\right]=\displaystyle \lim_(n\rightarrow \infty)\left[ (1)/(n)\right]=\boxed{0}

User NIKHIL NEDIYODATH
by
5.1k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.